2010
DOI: 10.1002/j.2168-9830.2010.tb01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Students Choose Engineering? A Qualitative, Longitudinal Investigation of Students' Motivational Values

Abstract: Background Recently published reports call for an increase in the number of engineering graduates and suggest appropriate characteristics that these graduates should embody. Accomplishing such change first requires understanding why students choose to pursue engineering degrees. Purpose (Hypothesis) Framed in motivation theory, our purpose was to better understand how students choose engineering by answering the question: How do engineering students' engineering‐related value beliefs contribute to their choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
307
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(334 citation statements)
references
References 39 publications
11
307
2
Order By: Relevance
“…Specifically, we investigate the impact of prior engineering-related work experiences on how this population approaches engineering design, and their development of an engineering identity. The work parallels prior work in engineering design protocols [11,12], and engineering identity development [7] in order to broaden the data pool as well as enable comparison of this target population versus the general engineering student population.…”
Section: Adult Engineering Studentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, we investigate the impact of prior engineering-related work experiences on how this population approaches engineering design, and their development of an engineering identity. The work parallels prior work in engineering design protocols [11,12], and engineering identity development [7] in order to broaden the data pool as well as enable comparison of this target population versus the general engineering student population.…”
Section: Adult Engineering Studentsmentioning
confidence: 87%
“…Research has looked at understanding the student experience and challenges in an effort to customize the different programs. Various studies have looked at reasons students have for entering STEM programs [5,6], while others have observed development of engineering identity as a reason for increased persistence [7]. The desire to have a diverse student population that leads to a diverse workforce has brought attention within engineering programs to the adult students.…”
Section: Adult Engineering Studentsmentioning
confidence: 99%
“…Attainment value, which is related to engineering identity (being an engineer is related to one's "sense of self"), has been found to be important for the persistence of engineering students during their undergraduate programs. Further, it has been found to be more important to engineering persistence than interest or perceived utility 13 . Other research on students' engineering identity has focused on the college years, exploring both engineering and professional identity development.…”
Section: Theoretical Framing Identitymentioning
confidence: 99%
“…However, Matusovich found that more women than men felt that engineering values did not align with their sense of self. [7]. For this reason, engineering concentrations with more obvious societal benefit, such as environmental and biomedical engineering, attract more female students [8].…”
Section: Social Consciousnessmentioning
confidence: 99%